Sulfur-doped graphene for efficient electrocatalytic N2-to-NH3 fixation - Li, Xia; Yang, Jiajia; Wang, Huanbo; Zhao, Runbo; Chen, Hongyu; Fang, Weihai; Asiri, Abdullah M; Xie, Fengyu; Cui, Ganglong; Sun, Xuping (Chemical communications (Cambridge, England), 2019)
Industrial NH3 synthesis mainly relies on the carbon-emitting Haber–Bosch process operating under severe conditions. Electrocatalytic N2-to-NH3 fixation under ambient conditions is an attractive approach to reduce energy consumption and avoid direct carbon emission. In this communication, sulfur-doped graphene (S-G) is proposed as an efficient and stable electrocatalyst to drive the nitrogen reduction reaction (NRR) under ambient conditions. In 0.1 M HCl, this S-G attains a remarkably large NH3 yield of 27.3 μg h−1 mgcat.−1 and a high Faradaic efficiency of 11.5% at −0.6 and −0.5 V vs. a reversible hydrogen electrode, respectively, much higher than those of undoped G (6.25 μg h−1 mgcat.−1; 0.52%). Density functional theory calculations reveal that carbon atoms close to substituted sulfur atoms are the underlying catalytic active sites for the NRR on S-G, and the related NRR mechanism is also explored.